Measuring how to evaluate the impact of doing student’s homework using the distance e-learning process in the computer science course, and access its efficiency in developing academic achievement - Al-Rabadi, Jad Salti (Journal of Educational and Psychological Sciences, 2021)
This study aimed to investigate the efficiency of teaching students on distance learning platforms and its impact on academic achievement. Specifically, it tried to answer the following question: “How to evaluate the impact of doing student’s homework using the distance e-learning process in the computer science course, and access its efficiency in developing academic achievement?”The study was conducted by using experimental methodology. The study samples consisted of 30 students from the ninth grade, at King Abdullah-II School for Excellence in Ajloun, Jordan. The first half of the samples represents the experimental-group that studied using specific teaching strategies and the homework method used the Internet platform for implementation and follow-up. The second half represents the control-group who studied with the same strategies, but used the traditional homework method within the classroom environment and follow-up traditionally.The efficiency evaluation for teaching the two groups was by preparing an achievement test consisted of 25 multiple-choice items. The study showed the following results: The experimental-group students who studied using homework via the internet platform outperformed the control-group students who studied using traditional homework, with a constant factor of 0.97.In light of the result, the researcher recommended a number recommendations: the necessity of using homework via Internet platform, considering individual differences in achievement by distributing duties in terms of ease and difficulty, using a reasonable duties amount so it doesn’t burden students, coordination between teachers of other subjects when assigning students’ homework, and finally recommendations to study other variables such as parents' academic level and teachers strategies of preparing homework.
Keywords: homework; online distance learning; computer-based teaching; student evaluation strategies